Lateral Junctions Based on Graphene with Different Doping Regions - R.M.В Balabai; A.G.В Lubenets (Журнал нано- та електронної фізики)
The valence electron density spatial distribution, the densities of electron states, the widths of valence and gap bands, the charges on core regions, the Coulomb potentials along the chosen directions of the lateral junctions of graphene/graphane, graphene/fluorographene and graphene/chlorographene, have been calculated in the framework of the density functional and ab initio pseudopotential theories. The considerable change of the electric charge has been fixed on the boundary of division in the planes of lateral junctions of graphene/graphane and graphene/fluorographene, which causes the appearance of the potential barriers on the boundary. After graphene being functionalized with different adsorbates, the relief of the Coulomb potential distribution turns from isotropic into anisotropic. The planar junction of graphene/graphane has the biggest leap in the potential relief. The biggest width of gaps of lateral planar junctions of graphene/graphane, graphene/fluorographene, graphene/chlorographene is that of graphene/graphane lateral junction.